PROBLEMS AND POLICIES OF RURAL DEVELOPMENT IN NYUNZU TERRITORY - C.T. AMURI KAMAKUMBI YAULI, (IJRDO - Journal of Social Science and Humanities Research, 2025)
The research on the problem and policy of rural development in Nyunzu territory aims to understand the challenges faced by this rural territory of the Democratic Republic of the Congo in terms of economic, social and environmental development. Nyunzu is a backward and isolated territory, characterized by precarious living conditions for its predominantly poor agricultural population. Also, the transfer of the active agricultural population into the mining sector and the ongoing inter-community conflict between Twa and Bantous especially in North Lukuga Sector further reinforce the poor living conditions of the population.The main problematic issues identified in the research concern limited access to basic services such as education, health and drinking water, as well as weak transport and communication infrastructure which hinders the economic development of the territory.Moreover, the increasing pressure on natural resources such as agricultural lands and forests due to a rapidly growing population contributes to environmental degradation.To address these challenges, the research sheds light on the different rural development policies and programs put in place by the Congolese government and international organizations in Nyunzu territory. These initiatives generally aim at improving access to basic services, promoting sustainable agriculture, strengthening the capacities of local communities and protecting natural resources.However, despite these efforts, obstacles persist in the implementation of these policies, such as corruption, lack of coordination among different development actors, and lack of participation of local communities in decision-making. Consequently, rural development in Nyunzu remains a complex challenge that requires a holistic and participatory approach to ensure sustainability and inclusiveness of development initiatives.In conclusion, the research highlights the importance of taking into account the local specificities and needs of rural communities in the planning and implementation of rural development policies in Nyunzu. It is essential to adopt an integrated and participatory approach that fosters the autonomy and resilience of local communities in their resource management and development.